Experimento da fluorescência: uma estratégia de aprendizagem para a introdução do modelo Atômico de Bohr no ensino de química - BALIEIRO, Ziran Cardoso (Instituto Federal do Amapá, 2021)
This work arises from a concern of the author about the lack of basic and fundamental knowledge of students about the structure of matter, the elemental disposition of atoms and mainly the structure proposed by Bohr's atomic model. The research proposes to apply the fluorescence experiment as a practical didactic resource in the classroom to align with the theory and, consequently, performance to elementary school students with a view to improving the teaching and learning of these subjects, later on, in high school. The methodology presented is based on bibliographic studies to survey the theoretical foundations of learning to understand how it occurs, supporting a practical model of stimulus and response by experimental observation, achieving significant learning for students. Six scientific experiments were proposed that use the effect of fluorescence as a phenomenon, using low-cost materials in classroom practices and subsequently an evaluation of the proposal through questionnaires for qualitative and quantitative analyzes with students of fundamental education (9º grade) of a public school in Macapá-AP. The results showed a great advantage in applying the methodology, since it allowed the student to interact with the activities and the same ones as subjects pointing out in speeches the need to carry out practical activities in Chemistry classes.